Spiritual Well Being in The Elderly - Safitri, Widya; Sugiharto, Dwi Yuwono Puji; Sutoyo, Anwar (Jurnal Bimbingan Konseling, 2020)
Spiritual well-being is one of the causes of the attitude of the elderly in everyday life. These conditions can experience changes depending on how the environment affects them. This study has the purpose of determining the psychological impact of factors caused can affect the condition of the spiritual well-being of the elderly. This study used a phenomenological research design using the research data sources of 2 elderly and five respondents (4 nurses, and one ustadzah) as informants. Data analysis using qualitative data analysis techniques model of Miles, and Huberman. The results of the study showed that spiritual well-being could experience an increase and decrease. This is influenced by several factors such as attention from relatives, full of desires, attention from nurses and elderly colleagues, and the role of religious teachers in assisting the elderly. Increased spiritual well-being is characterized by a cheerful attitude, not easy to complain and more passionate about reciting. Meanwhile, the decline in spiritual well-being often leads to an attitude of despair, anger, and even rebellion.